2003
DOI: 10.1002/anie.200352737
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Greatly Improved Reversible O2 Binding in a Structurally Modulated μ‐η22‐Peroxodicopper(II) Complex with Room‐Temperature Stability

Abstract: Facile O2 release from an oxyhemocyanin model has been achieved for the first time, with the new room‐temperature‐stable μ‐η2:η2‐peroxodicopper complex [Cu2O2(L2)]2+ (1). X‐ray structural and spectroscopic studies on 1 show that elongation of the CuO bonds, induced by the bridgehead methyl groups of L2, is responsible for the ease of O2 release. CO/O2 binding by 1, monitored by UV/Vis spectroscopy (see picture), is completely reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…[6] Dicopper biosites are known to catalyze oxidations of various hydrocarbons,s uch as aromatic compounds and alkanes. [7] Va rious dicopper complexes have been developed for O 2 binding, [8] but are less studied as catalysts for the oxidation of methane and benzene. [9] Herein, it was found that ad icopper complex with the dinucleating ligand 1,2bis[2-[bis(2-pyridylmethyl)aminomethyl]-6-pyridyl]ethane [10] (6-hpa), [Cu 2 (m-OH)(6-hpa)](ClO 4 ) 3 (1), exhibits high catalytic activity in selective hydroxylation of benzene with H 2 O 2 .…”
mentioning
confidence: 99%
“…[6] Dicopper biosites are known to catalyze oxidations of various hydrocarbons,s uch as aromatic compounds and alkanes. [7] Va rious dicopper complexes have been developed for O 2 binding, [8] but are less studied as catalysts for the oxidation of methane and benzene. [9] Herein, it was found that ad icopper complex with the dinucleating ligand 1,2bis[2-[bis(2-pyridylmethyl)aminomethyl]-6-pyridyl]ethane [10] (6-hpa), [Cu 2 (m-OH)(6-hpa)](ClO 4 ) 3 (1), exhibits high catalytic activity in selective hydroxylation of benzene with H 2 O 2 .…”
mentioning
confidence: 99%
“…The 29 Si and 13 C CPMAS NMR spectra for M1 are presented in Figure S2 in the Supporting Information. Materials M1 and M2 were formed with a high degree of polycondensation, as the 29 Si NMR spectrum displayed mainly T 3 and Q 4 substructures.…”
Section: Structural and Textural Characterizationmentioning
confidence: 99%
“…Materials M1 and M2 were formed with a high degree of polycondensation, as the 29 Si NMR spectrum displayed mainly T 3 and Q 4 substructures. The T n signals are indicative of the incorporation and high condensation of the organosilane derivative within the inorganic silica.…”
Section: Structural and Textural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of these compounds are influenced by various factors such as the ligands and solvents used, reaction temperature, metal-ligand ratio, thus producing a variety of coordination geometries. Studies to explore the relationship between the oxidation state of the copper(II) centre and the geometry of the complex as well as the coordinating atoms have been carried out [8][9][10][11][12]. As a result it has become possible to control the oxidation/reduction behaviour using certain ligands.…”
Section: Introductionmentioning
confidence: 99%